The exploration and evaluation of groundwater units in the Van Rynevelds Pass Dam Basin, north of Graaff-Reinet, Cape Province - Woodford, A C (Rhodes University, Faculty of Science, Department of Geography, 1989)
This thesis deals with a groundwater investigation conducted in the Van Rynevelds Pass Dam basin, north of Graaff-Reinet, in the Cape Province. The objective of the study was to assess the groundwater potential of the basin in terms of its development and exploitation as a municipal supply. In order to achieve this objective, fieldwork was carried out involving a hydrocensus, geological/geophysical mapping, drilling, aquifer testing and hydrochemical sampling. The fieldwork was conducted during the period January 1983 to February 1984. The investigation revealed that the most significant ground water occurrence in the study area is an alluvial/weathered bedrock aquifer (Graaff-Reinet aquifer ) . The volume of ground water stored in the Graaff-Reinet aquifer is in the order of 27 x 10â ¶ mÂ³, while its exploitation potential is conservatively estimated at 9 300 mÂ³/day. However, the quality of this water is poor and should be blended with dam water or better quality groundwater. Two minor fractured aquifer units were also identified.
Keywords: Aquifers -- South Africa -- Graaff-Reinet; Hydrogeology -- South Africa; Groundwater -- South Africa -- Graaff-Reinet